The "foreignness" of the foreign woman in Proverbs 1-9 : a study of the origin and development of a Biblical motif - Tan, Nancy Nam Hoon (Beihefte zur Zeitschrift für die alttestamentliche Wissenschaft ;, 2008)
This study is on the figure [Shh zdh] and [nchdh] also commonly called the 'Strange Woman' in Proverbs 1-9. It is an attempt to understand the meaning which defines her, and the origin and development of her motif. The first part argues against defining her as a sexual predator, but as an ethnic foreigner according to the lexical studies of [Zd] and [nchd] It traces her origin within the Hebrew scripture, the legal documents and especially to the DtrH's portrayal of foreign women/wives. Hence, it distinguishes the two motifs: the motif of the adulteress and the motif of the foreign woman; the latter, which symbolizes the temptation to apostasy. The study will then go on to explain how the writer of Proverbs 1-9 employs this motif of the foreign woman in his poetic composition. The second part tracks the development of this motif through the subsequent Jewish Wisdom literature and observes how it changes and loses the 'foreignness' of her original motif in Eccl. 7:26; 4Q184; LXX Proverbs; Hebrew Ben Sira; Greek Ben Sira; and finally disappears in Wisdom of Solomon. It proffers to understand this gradual transformation against a background of social and religious change.